1998
DOI: 10.1051/kmae:1998026
|View full text |Cite
|
Sign up to set email alerts
|

Effets du soja et des phyto-oestrogènes sur la vitellogénèse et l'endocrinologie stéroïdienne de la truite arc-en-ciel et de l'esturgeon sibérien. Approches in vivo et in vitro

Abstract: RÉSUMÉLa mise au point d'un test de sexage des esturgeons sibériens, basé sur la détection de la vitellogénine (VTG) plasmatique, a permis de mettre en évidence cette protéine complexe oestrogéno-dépendante dans le plasma des poissons femelles, mâles et immatures de cette espèce. L'hypothèse d'une contamination oestrogénique d'origine environnementale a été confirmée par un test basé sur l'administration de différents aliments. Chez les témoins sans oestrogènes, la VTG disparaissait en quelques Semaines du pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Further analyses in agnathan species would be valuable due to their evolutionary position in the vertebrate lineage. In gnathostoma, data are unfortunately missing in the primitive ray-finned bony fishes, and to our knowledge, only one preliminary study indicated that testosterone was bound in blood of a chondrostean fish, the Siberian sturgeon (Acipenser baerii, Acipenseriformes) (Bennetau-Pelissero et al, 1998).…”
Section: Circulating Shbgmentioning
confidence: 93%
“…Further analyses in agnathan species would be valuable due to their evolutionary position in the vertebrate lineage. In gnathostoma, data are unfortunately missing in the primitive ray-finned bony fishes, and to our knowledge, only one preliminary study indicated that testosterone was bound in blood of a chondrostean fish, the Siberian sturgeon (Acipenser baerii, Acipenseriformes) (Bennetau-Pelissero et al, 1998).…”
Section: Circulating Shbgmentioning
confidence: 93%
“…These kind of studies were performed with fish SBP [86] and with Human SHBG [87,88] and α Feto-Protein [89]. In humans genistein was also shown in vitro to induce SHBG synthesis by the liver [90].…”
Section: In Vitro Effectsmentioning
confidence: 99%